Spring phenological escape is critical for the survival of temperate tree seedlings. (21st May 2021) - Lee, Benjamin R.; Ibáñez, Inés
Abstract: Understorey plants in deciduous forests often rely on access to ephemeral light availability before the canopy closes in spring and after the canopy reopens in fall, a strategy commonly referred to as phenological escape. Although there is evidence for a relationship between understorey plant phenology and demographic performance, a mechanistic link is still missing. In this study, we bridged this gap by estimating annual carbon assimilation as a function of foliar phenology and photosynthetic capacity for seedlings of two temperate tree species that commonly co‐occur across eastern North America. We then modelled the relationship between estimated carbon assimilation and observed seedling survival and growth. Our results indicate that seedlings of both species strongly depend on spring phenological escape to assimilate the majority of their annual carbon budget and that this mechanism significantly affects their likelihood of survival (but not growth). Foliar desiccation also played a strong role in driving patterns of seedling survival, suggesting that water availability will also help shape seedling recruitment dynamics. We found only weak associations between seedling senescence in fall and annual carbon assimilation, suggesting that phenological escape in fall plays a relatively minor role in seedling demographic performance. Our results indicate that spring phenological escape is critical for survival of these temperate tree species, and thus, any changes to this dynamic associated with climate change could strongly impact these species' recruitment. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.